Impact of transcranial magnetic stimulation on motor function in children with acquired brain injury: a scoping review protocol - Rajat Gupta; Chandrasekar Rathinam; Vikram Mohan; Peter Bill; Derick Yates; Janet Peirson (BMJ Publishing Group, 2023)
Background Children with severe acquired brain injury (ABI) require early and effective neurorehabilitation provision to promote a good long-term functional outcome. Transcranial magnetic stimulation (TMS) has been used to improve motor skills for children with cerebral palsy but there is limited material supporting its use in children with ABI who have a motor disorder.Objective To systematically answer what the TMS intervention effects are on motor function in children with ABI as reported in the literature.Methods and analysis This scoping review will follow Arksey and O'MaIIey's scoping review methodological framework. A comprehensive computerised bibliographic databases search will be performed in MEDLINE, EMBASE, CINAHL, Allied and Complementary Medicine, BNI, Ovid Emcare, PsyclNFO, Physiotherapy Evidence Database, Cochrane Central Register using keywords related to TMS and children with ABI.Studies that examine the effect of TMS intervention on motor function as either a primary or secondary objective will be included for this review. Study design and publication detail, participant demographic details, type and severity of ABI and other clinical information, TMS procedure, associated therapy intervention, comparator/control parameters and the outcome measure used data will be gathered.The International Classification of Functioning, Disability and Health for Children and Youth framework will be used to report the TMS effect in children with ABI. A narrative synthesis of the findings describing the therapeutic effects of TMS intervention, limitations and adverse effects will be synthesised and reported. This review will help to summarise the existing knowledge base and to guide further research areas. This review outcome may help to evolve therapists' role to next-generation technology-based neurorehabilitation programmes.Ethics and dissemination No ethical approval is required for this review as we will be collecting data from previously published studies. We will present the findings at scientific conferences and publish in a peer-review journal.